CG-MS, Radical Scavenging, Acetylcholinesterase Inhibition, Antifungal and Molecular Docking Studies of Essential Oil from the Leaves of Tapirira guianensis Aubl - , Daniel P. de Oliveira; , Lucas S. Frota; , Sara I. C. Gomes Barbosa; , Francisco F. S. Lopes; , José R. G. Neto; , Marcia M. Marinho; , Emmanuel S. Marinho; , Jacilene Silva; , Júlio César S. Prado; , Raquel Oliveira dos S. Fontenelle; , Selene M. de Morais (Archives of Current Research International, 2024)
The species Tapirira guianensis Aubl is used in folk medicine to treat leprosy, diarrhea, and syphilis. The present study aims to evaluate the chemical composition and the antioxidant, anticholinesterase, and antifungal potential of the essential oil from T. guianensis leaves. The plant material was collected at Arco Estadual do Cocó, with prior authorization from the Municipal Environment Department. The essential oil was extracted through the hydrodistillation process with a Clevenger-type apparatus, and the constituents were evaluated through Gas Chromatography coupled to Mass Spectrometry (GC-MS). The antioxidant potential was assessed through free radicals: DPPH (2,2-diphenyl-1-picrylhydrazyl) and ABTS+ (2,2-azinobis(3-ethylbenzothiazoline-6-sulfonic acid)) in a 96-well plate. Antifungal activity was evaluated using the Clinical Laboratory Standards Institute - M38-A protocol (CLSI, 2018). Gas chromatography coupled with mass spectrometry revealed the presence of constituents such as eugenol (59.00%), α-copaene (0.40%), β-caryophyllene (29.91%), α-humulene in T. guianensis. The essential oil demonstrated very promising antioxidant and anticholinesterase potential in In vitro studies. Molecular docking regarding acetylcholinesterase enzyme inhibition revealed that α-copaene has superior action compared to the drug physostigmine. The results of molecular docking for Candida albicans showed that α-copaene and α-humulene interacted in the same binding region as the PepA inhibitor against SAP5. This indicates their action is similar to the aspartic protease inhibitor, in addition to the possibility of a synergistic effect with the drug fluconazole. This is the first study of the biological potential of the essential oil from T. guianensis leaves, thus revealing its high potential for future studies in the scientific community. Therefore, we can infer that the essential oil of T. guianensis is a source of antioxidant, anticholinesterase, and antifungal constituents, with promising therapeutic potential in the management of Alzheimer's disease and Candida infections.